1999
DOI: 10.22358/jafs/68942/1999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linseed oil fatty acid calcium salts and vitamin E on milk yield and composition

Abstract: Eight Holstein Red-and-White cows were used in two squares of a 4 x 4 Latin square design experiment and fed for 84 days (weeks 4-16 of lactation) with Ca salts of fatty acids (CaSFA) of linseed oil and animal fat. Experimental diets contained 0, 3, 6 and 9% CaSFA (on DM basis) and vitamin E at doses of 40 and 168 mg kg" 1 DM of concentrate (DM). Cows were fed grass silage and 0.280 kg of concentrate per kg of milk. Average FCM yield was 24.0±0.5 kg/d A with 40.0±0.7 and 31.2±0.3 g/kg" 1 fat and protein, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Most studies have found that dietary fat supplements, by increasing the amount of fat or leaving it unchanged, decrease the protein content, especially when the fat supplements in the diet exceed 2-2.5% of dry matter Brzóska et al, 1999). Similar results were obtained after duodenal infusion of fatty acids (Romo et al, 2000).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Most studies have found that dietary fat supplements, by increasing the amount of fat or leaving it unchanged, decrease the protein content, especially when the fat supplements in the diet exceed 2-2.5% of dry matter Brzóska et al, 1999). Similar results were obtained after duodenal infusion of fatty acids (Romo et al, 2000).…”
Section: Discussionmentioning
confidence: 66%
“…The data obtained indicate that giving cows 316, 614 or 940 g of CSFA results in a surplus of dietary energy intake compared with the energy secreted in milk, leading to increased body weight. The reaction of cows to the source of dietary fat is a typical response confirmed in many experiments using CSFA in dairy cow nutrition (Aii et al, 1991;Chouinard et al, 1997;Brzóska et al, 1999). Analysis of the cows' plasma showed a typical reaction to the supplement of unsaturated dietary fat, consisting in a significant increase in the level of plasma triglycerides and a decrease in the levels of total and HDL cholesterol.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations